Seed dispersal and fine-scale genetic structuring in the asexual Nigritella miniata (Orchidaceae) in the Alps. (26th April 2019) - Hedrén, Mikael; Lorenz, Richard
Abstract: Orchids have minute, air-filled seeds and are considered to be efficient dispersers and colonizers. However, empirical studies show that most seeds fall within a metre of the mother plant in orchids, and that individuals standing close to each other are often closely related. A poor contribution to gene dispersal by seeds may be compensated for by more efficient dispersal by pollen, but in autogamous or agamospermous orchids this component is not available. Here, we used two highly variable simple sequence repeat loci to analyse fine-scale genetic structure in the agamospermous orchid Nigritella miniata, which is widespread in alpine grasslands in the Dolomites. We studied a densely populated area of 30 × 50 m and an enlarged area of 100 × 500 m with more scattered occurences. Sp statistics, describing the decrease in relatedness with geographical distance, were 0.1073 and 0.0609, respectively, and were among the highest values recorded for the orchid family, revealing a strong genetic structuring. However, some genotypes in the studied area were distributed at distances up to 26.5 km in the Dolomites, which suggests that long-distance seed dispersal occurs occasionally and that populations separated by long distances can still be parts of the same meta-population system.